1999
DOI: 10.1111/1467-8624.00090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residential Instability on Head Start Children and Their Relationships with Older Siblings: Influences of Child Emotionality and Conflict between Family Caregivers

Abstract: This study examined the influence that residential dislocations have on child behavior problems, depression, peer competence, cognitive competence, and the quality of sibling relations in a sample of 70 Head Start children, aged 32 to 67 months, and their older brothers and sisters, aged 48 to 155 months. This was the first study to investigate the sibling relationship in the context of high residential mobility. Information on child characteristics was obtained from mothers and teachers. Sibling data (warmth/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 60 publications
2
22
0
1
Order By: Relevance
“…Results of the existing studies diverge from both the school-age literature and from one another. Some research indicates that residential mobility in the early years does not have an impact on cognitive or academic ability (Anderson, 2012;Coley, Leventhal, Lynch, & Kull 2013;Stoneman, Brody, Churchill, & Winn, 1999;Ziol-Guest & McKenna, 2014). This finding is inconclusive, however, as studies generally rely on small (e.g.…”
Section: Residential Mobility and Child Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the existing studies diverge from both the school-age literature and from one another. Some research indicates that residential mobility in the early years does not have an impact on cognitive or academic ability (Anderson, 2012;Coley, Leventhal, Lynch, & Kull 2013;Stoneman, Brody, Churchill, & Winn, 1999;Ziol-Guest & McKenna, 2014). This finding is inconclusive, however, as studies generally rely on small (e.g.…”
Section: Residential Mobility and Child Wellbeingmentioning
confidence: 99%
“…This finding is inconclusive, however, as studies generally rely on small (e.g. Stoneman et al, 1999) or unrepresentative (e.g., Anderson, 2012) samples. Diverging from the other studies, Schmitt, Finders, & McClelland (2015) do find mobility is negatively associated with achievement in the fall term of pre-school in a sample of children primarily from Head Start.…”
Section: Residential Mobility and Child Wellbeingmentioning
confidence: 99%
“…However, the NICHD study found that, while child care instability during the first two years of life was related to greater mother-reported behavior problems, this effect was no longer statistically significant by 3 years of age so the effects may be short-lived (NICHD Early Child Care Research Network, 1998). Furthermore, in order to better understand the effects of child care instability, it would appear important to consider a number of additional child-and family-related variables that have been found to be associated with children's behavioral outcomes, including the timing, intensity, and continuity of maternal employment during the preschool years (Baydar & Brooks-Gunn, 1991), the child's temperament (Stoneman, Brody, Churchill, & Winn, 1999), and reasons for changes in care such as marital dissolution, changes in patterns of employment, and residential moves (Ackerman, Kogos, Youngstrom, Schoff, & Izard, 1999;Hoglund & Leadbeater, 2004).…”
Section: Hyperactivity-inattentionmentioning
confidence: 99%
“…A substantial body of literature demonstrates that frequent residential moves are associated with threats to optimal child and family functioning that include lower cognitive and social functioning among children, as well as heightened maternal psychological distress and parenting stress (Astone and McLanahan 1994;Busacker and Kasehagen 2012;Coley et al 2013;Pribesh and Downey 1999;Simpson and Fowler 1994;Stoneman et al 1999). Despite these consequences of residential mobility, surprisingly limited empirical attention has attempted to comprehensively illuminate the factors that predict mobility.…”
Section: Introductionmentioning
confidence: 99%